Responses to different dosages of monocrotophos and deltamethrin on chlorophyll and protein contents of chickpea - Dixit, R; Rani, M; Kumar, J (SAARC Journal of Agriculture, 2023)
Chickpea (Cicer arietinum) is a major legume food crop. Its seeds are rich in carbohydrates, protein, vitamin B, and other minerals. For better seed output and protein content, various factors viz; proper light conditions, and freedom from insect pests are necessary. Many insect pests play a damaging role in chickpea production and hence pest control is key to better production. This study was carried out at the experimental sites of Chhatrapati Shahu Ji Maharaj University, Kanpur, India to assess the responses to different dosages of monocrotophos pesticides on chlorophyll and protein contents in Chickpea. Different doses of monocrotophos viz., control, 0.5%, 1%, 1.5%, 2%, 2.5%, 5% 7.5%, and 10% were applied to seeds before sowing. Quantitative analysis of plants for chlorophyll content was done on a per-plant basis, The plant tissues were weighed and the analysis was done on an mgg-1 fresh weight basis. Chlorophyll content was estimated by extracting 80% acetone and determined spectrophotometrically and the quantification was done by the Arnon method (1949). The protein content was also estimated spectrophotometrically. The best results were obtained at 0.5% pesticide concentration. The total chlorophyll content was 1.662 mgg-1 for control and 1.671mgg-1 for 0.5% and decreased with the increasing concentration of monocrotophos pesticide. The protein content was highest, 28.41 mgg-1 at 0.5%, as compared to 27.45 mgg-1 at the control and decreased for increasing concentrations of monocrotophos. The same trend of results was recorded for different doses of deltamethrin. SAARC J. Agric., 21(1): 217-225 (2023)